Connecting arrowheads: Differential transmission of information at the dawn of the Bronze Age - Jiménez-Puerto, Joaquín (Journal of Lithic Studies, 2024)
The study of the relationships between prehistoric social groups is one of the main targets in present day archaeology. A useful tool to entangle this issue is social network analysis (SNA). Some of the advantages brought by this mathematic approach refer to the possibility of studying relationships through the material culture items, or its capability to integrate different scales of analysis (macro-micro). Moreover, SNA combined with the application of bayesian statistical methods of chronological attribution can create long range diachronic series of relational information, connected with prehistoric social groups dynamics. This methodology enables archaeologists to study archaeological big data from a totally different perspective, not only focused on a descriptive or morphometric point of view. The objective of this work is to apply an SNA procedure, together with a recently developed bayesian tool of chronological attribution, to archaeological sites located in the East of the Iberian Peninsula during the 4th and 3rd millennium cal. BCE using chert arrowheads as an archaeological proxy, due to the chronologic implications their morphology has, in the referred geographic frame. It is our specific target to analyse the transition between the Bell-Beaker world and the Bronze Age, through the differential transmission of information and the time-space variability present in the archaeological record, through the study of relationships between chert arrowheads assemblages. In order to do so, we will build a relational framework between the social communities present in the Late Neolithic-Copper Age through the chert arrowheads morphologic typologies, and we will apply SNA to characterize the resulting networks. Furthermore, we will propose a new metric to quantify the cultural fragmentation using community detection algorithms, in a diachronic axis, to identify groups of sites with homogeneous technological behaviour, to check the initial hypothesis which points to the existence of periods of cultural homogeneity followed by others in which fragmentation-regionalization is dominant.